Comparative evaluation of piezoelectric response of electrospun PVDF (polyvinilydine fluoride) nanofiber with various additives for energy scavenging application. Issue 6 (3rd June 2017) - Mokhtari, F.; Shamshirsaz, M.; Latifi, M.; Asadi, S.
Abstract: Energy harvesting using piezoelectric nanomaterial provides an opportunity for advancement toward self-powered electronics. The fabrication complexity and limited power output of these nano/micro generators have hindered these advancements. This paper introduced a ﬂexible and light weight nanogenerator package that was obtained by variety of additives (ZnO, CNT, LiCl, PANI) and try to have comparisons between them to choose appropriate one base on final application. Performances of these additives were evaluated using Fourier Transform Infrared, Scanning Electron Microscopy, Impedance analyzer, and traction-compression machine. The excitation method is based on low velocity impact test by falling down a ball on samples. Results show that for all additives there is a direct connection between β phase formation and output voltage. CNT nanoparticles lead to have more β Phase formation and higher output voltage (0.9 V) for electrospun web with 230 μm thickness. The results imply promising applications, as an enhanced efficiency energy-scavenging interface, for various wearable self-powered electrical devices and systems.